2014
DOI: 10.3390/ijms151120134
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Associated with the Efficacy of Photodynamic Therapy in Biliary Tract Cancer Cell Lines

Abstract: Photodynamic therapy (PDT) is a palliative treatment option for unresectable hilar biliary tract cancer (BTC) showing a considerable benefit for survival and quality of life with few side effects. Currently, factors determining the cellular response of BTC cells towards PDT are unknown. Due to their multifaceted nature, microRNAs (miRs) are a promising analyte to investigate the cellular mechanisms following PDT. For two photosensitizers, Photofrin® and Foscan®, the phototoxicity was investigated in eight BTC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 106 publications
1
14
0
Order By: Relevance
“…with the atypical expression of miR-200a, miR-200b, and miR200c. Although our investigations were in consonance with several others in varied types of cancers (such as Prostate [15], Breast [37,38], Ovary [16,39,40], NSCLC [10,41], Bladder [42], Hepatocellular [35,43], Pancreatic [44], Biliary duct [45], Endometrial endometrioid [46], Anaplastic thyroid [47]) and discrete populations throughout the world [16,48], few studies suggested otherwise such as the study by Xu et al [49] which indicated that the expression levels of miR-200a were significantly down-regulated in late-stage disease (FIGO III ? IV) compared with early stage (FIGO I ?…”
Section: Discussionsupporting
confidence: 72%
“…with the atypical expression of miR-200a, miR-200b, and miR200c. Although our investigations were in consonance with several others in varied types of cancers (such as Prostate [15], Breast [37,38], Ovary [16,39,40], NSCLC [10,41], Bladder [42], Hepatocellular [35,43], Pancreatic [44], Biliary duct [45], Endometrial endometrioid [46], Anaplastic thyroid [47]) and discrete populations throughout the world [16,48], few studies suggested otherwise such as the study by Xu et al [49] which indicated that the expression levels of miR-200a were significantly down-regulated in late-stage disease (FIGO III ? IV) compared with early stage (FIGO I ?…”
Section: Discussionsupporting
confidence: 72%
“…As a group of non-coding RNAs, miRNAs exist in a wide variety of organisms and have been demonstrated to have important biological functions with complicated mechanisms of action, each having single or multiple target genes to regulate (14)(15)(16). miRNA-21 is a ubiquitous miRNA, which is expressed at abnormal levels in numerous types of cancer, including colorectal cancer, bile duct carcinoma, lymphoma, multiple myeloma and glioma, suggesting that it is an oncogene (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Electric field-assisted delivery of photofrin, electroporation, to the breast adenocarcinoma cells (MCF-7) and normal Chinese hamster ovary cells (CHO) has been found to enhance cellular uptake of Photofrin, which reduces effective dose and exposure time diminishing side effects of the therapy [30]. The efficacy of PDT is also affected by combining with some other drugs, such as Celecoxib, Dihydroartemisinin (DHA), and microRNAs (miRs), which regulate either the signaling pathway or gene expression in some cancer cell lines [31,32,33]. For example, overexpression of miR-130a could theoretically lead to more efficient PDT in resistant cell lines affecting adaptation to ROS stress, such as decreasing the expression of Sirtuin protein family, which regulates FOXO3a/Bim pathway and participates in a lot of neurodegenerative disorders [33,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of PDT is also affected by combining with some other drugs, such as Celecoxib, Dihydroartemisinin (DHA), and microRNAs (miRs), which regulate either the signaling pathway or gene expression in some cancer cell lines [31,32,33]. For example, overexpression of miR-130a could theoretically lead to more efficient PDT in resistant cell lines affecting adaptation to ROS stress, such as decreasing the expression of Sirtuin protein family, which regulates FOXO3a/Bim pathway and participates in a lot of neurodegenerative disorders [33,34,35]. An upconversion nanoparticle-Zinc phthalocyanine based nanophotosensitizer for PDT has been proven to result in the high 1 O 2 production, leading to a secure and efficient PDT treatment [36].…”
Section: Discussionmentioning
confidence: 99%